Experimental observations of communication in blackout, topological waveguiding and Dirac zero-index property in plasma sheath - Li Jianfei; Wang Ying; Zhou Zhongxiang; Yao Jingfeng; Liu Jianlong; Lan Zhihao; Yuan Chengxun (Nanophotonics, 2023)
The plasma sheath causes the spacecraft’s communication signal to attenuate dramatically during the re-entry period, which seriously threatens the astronauts. However, valid experimental protocols have not been obtained hitherto. To realize the propagation of electromagnetic waves in negative permittivity background of the plasma sheath, alumina columns are embedded in the plasma background to form plasma photonic crystals, which can support the coupling of evanescent waves between the alumina columns. We experimentally demonstrate the realization of communication in blackout scenario by achieving a complete passing band in the plasma cutoff region. For high frequency communications in the plasma sheath, electromagnetic wave propagation based on topological edge states is also experimentally demonstrated. Furthermore, we realize a triply-degenerate Dirac cone formed dynamically at the center of the Brillouin zone by modulating the electron density, where electromagnetic wave exhibits high transmittance and does not experience phase accumulation at the Dirac point. Our work thus not only provides an effective approach to overcome the communication blackout problem, but the design can also be served as a promising experimental platform to explore topological electromagnetic phenomena.